An Expedient Synthesis, Acetylcholinesterase Inhibitory Activity, and Molecular Modeling Study of Highly Functionalized Hexahydro-1,6-naphthyridines - Almansour, Abdulrahman I.; Kumar, Raju Suresh; Arumugam, Natarajan; Basiri, Alireza; Kia, Yalda; Ali, Mohamed Ashraf (Hindawi Publishing Corporation, 2015)
A series of hexahydro-1,6-naphthyridines were synthesized in good yields by the reaction of 3,5-bis[(E)-arylmethylidene] tetrahydro-4(1H)-pyridinones with cyanoacetamide in the presence of sodium ethoxide under simple mixing at ambient temperature for 6–10 minutes and were assayed for their acetylcholinesterase (AChE) inhibitory activity using colorimetric Ellman’s method. Compound 4e with methoxy substituent at ortho-position of the phenyl rings displayed the maximum inhibitory activity with IC50 value of 2.12